Comparative Metagenomics of Cellulose- and Poplar Hydrolysate-Degrading Microcosms from Gut Microflora of the Canadian Beaver (Castor canadensis) and North American Moose (Alces americanus) after Long-Term Enrichment - Wong, Mabel T.; Wang, Weijun; Couturier, Marie; Razeq, Fakhria M.; Lombard, Vincent; Lapebie, Pascal; Edwards, Elizabeth A.; Terrapon, Nicolas; Henrissat, Bernard; Master, Emma R. (Frontiers in Microbiology, 2017)
To identify carbohydrate active enzymes (CAZymes) that might be particularly relevant for wood fibre processing, we performed a comparative metagenomic analysis of digestive systems from Canadian beaver (Castor canadensis) and North American moose (Alces americanus) following three years of enrichment on either microcrystalline cellulose or poplar hydrolysate. In total, 9386 genes encoding CAZymes and carbohydrate binding modules (CBMs) were identified, with up to half predicted to originate from Firmicutes, Bacteroidetes, Chloroflexi and Proteobacteria phyla, and up to 17% were encoded by unknown phyla. Both PCA and hierarchical cluster analysis distinguished the annotated glycoside hydrolase (GH) distributions identified herein, from those previously reported for grass-feeding mammals and herbivorous foragers. The CAZyme profile of moose rumen enrichments also differed from a recently reported moose rumen metagenome, most notably by the absence of GH13-appended dockerins. Consistent with substrate-driven convergence, CAZyme profiles from both poplar hydrolysate-fed cultures differed from cellulose-fed cultures, most notably by increased numbers of unique sequences belonging to families GH3, GH5, GH43, GH53, and CE1. Moreover, pairwise comparisons of moose rumen enrichments further revealed higher counts of GH127 and CE15 families in cultures fed with poplar hydrolysate. To expand our scope to lesser known carbohydrate-active proteins, we identified and compared multi-domain proteins comprising both a CBM and domain of unknown function (DUF) as well as proteins with unknown function within the 416 predicted polysaccharide utilization loci (PULs). Interestingly, DUF362, identified in iron-sulphur proteins, was consistently appended to CBM9; on the other hand, proteins with unknown function from PULs shared little identity unless from identical PULs. Overall, this study sheds new light on the lignocellulose degrading capabilities of microbes originating from digestive systems of mammals known for fibre-rich diets, and highlights the value of enrichment to select new CAZymes from metagenome sequences for future biochemical characterization.